TEACHING PROFESSIONAL VOCABULARY: CHALLENGES AND STRATEGIES FOR MEDICAL STUDENTS - Saparbaeva Saltanat Omirbaevna (Web of Journals Publishing, 2025)
The process of teaching professional vocabulary for medical students is very important for their future professional activities. To work in the medical field, students need to have not only clinical skills, but also excellent knowledge of professional terminology. Medical terminology is complex and spans many fields, so the process can be overwhelming for students. This article examines the challenges of teaching professional vocabulary to medical students and strategies to address them.
Keywords: Medicine, terminology, terms, difficulties, Latin language, anatomical diagrams, meaning